CRITERION FOR DETERMINATION OF LIMITING STATE IN CONDITIONS OF NON-LINEAR ELASTIC CONSTRUCTION BEHAVIOR - O. L. Shwed (Наука и техника)
A fluidity criterion is obtained as an exact solution of a differential equation expressing a preservation principle of elastic deformation potential nature in the active process. The criterion is intended for exposure of construction elements where irreversible deformation processes are initiated. The construction material is supposed to be isotropous and possibly heterogeneous.